Lindane removal using Streptomyces strains and maize plants: a biological system for reducing pesticides in soils - Alvarez, Analia (2015)
Background and aims: Plants and contaminant-degrading microbes are a suitable combination for the remediation of pesticides. The aim of this study was to evaluate the effectiveness of Streptomyces strains cultured with maize plants in relation to lindane removal.Methods: Four Streptomyces strains were cultured and added as both single and mixed cultures, along with maize plants, to artificially polluted hydroponic systems and soils. The effectiveness of the resulting soil bioremediation was then evaluated through phytotoxicity testing using lettuce seedlings.Results: In the hydroponic and soil experiments, similar levels of lindane removal were recorded in the inoculated and non-inoculated systems where maize plants were introduced. However, the vigor index (VI) of the maize plants was highest when grown in inoculated and artificially polluted soil. In the phytotoxicity assay, the VI of the lettuce seedlings increased with increasing bioremediation time for the soils, thus indicating the effectiveness of the process.Conclusions: Similar levels of lindane removal were recorded in both inoculated and non-inoculated planted systems, indicating that pesticide removal was not significantly affected by the bacterial inoculant. However, inoculation an actinobacteria consortium led to an increase in the VI of the maize and protected the plants against the existing toxicity. Furthermore, maize plants may attenuate the transient toxic effects of microbial lindane degradation.